Unraveling global impacts of climate change on amphibians distributions: A life-history and biogeographic-based approach - Alves-Ferreira, Gabriela; Talora, Daniela C.; Solé, Mirco; Cervantes-López, Martín J.; Heming, Neander M. (Frontiers in Ecology and Evolution, 2022)
Climate change can affect species distribution patterns in three different ways: leading species to disperse to new suitable areas, causing them to adapt to new climatic conditions, or driving them to extinction. However, the biological and geographical traits that lead to these different responses remain poorly explored. Here, we evaluated how ecological and biogeographic traits influence amphibians’ response to climate change. We performed a systematic review searching for studies that evaluated the effects of future climate change on amphibian’s distribution. Our research returned 31 articles that projected the distribution of 331 amphibians. Our results demonstrate that species inhabiting an elevation above 515 m will lose a significant portion of their climatically suitable area. We also found that as isothermality increases, the amount of area suitable in response to climate change also increases. Another important discovery was that as the size of the baseline area increases, the greater must be the loss of climatically suitable areas. On the other hand, species with very small areas tend to keep their current climatically suitable area in the future. Furthermore, our results indicate that species that inhabit dry habitats tend to expand their suitable area in response to climate change. This result can be explained by the environmental characteristics of these habitats, which tend to present extreme seasonal climates with well-defined periods of drought and rain. We also found that anurans that inhabit exclusively forests are projected to lose a greater portion of their suitable areas, when compared to species that inhabit both forest and open areas, wetlands, and dry and rupestrian environments. The biogeographical realm also influenced anuran’s range shifts, with Afrotropical species projected to expand their geographical ranges. The assessment of climate change effects on amphibian distribution has been the focus of a growing number of studies. Despite this, some regions and species remain underrepresented. Current literature evaluates about 4% of the 7,477 species of Anura and 8% of the 773 species of Caudata and some regions rich in amphibian species remain severely underrepresented, such as Madagascar. Thus, future studies should focus on regions and taxas that remains underrepresented.